Pengaruh Kepemilikan Publik, Kepemilikan Manajerial, Ukuran Perusahaan, dan Direksi Gender Diversity terhadap Nilai Perusahaan - Annisa Atikah Haura; Fahmi Roy Dalimunthe; Ali Sadikin (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2025)
This study aims to examine and analyze the influence of public ownership, managerial ownership, firm size, and board gender diversity on firm value in banking sub-sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The research method used is quantitative with a causality approach. The population of this study consists of all banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023, totaling 47 companies. The sampling technique used in this study is purposive sampling, with specific criteria resulting in a sample of 23 companies. The data analysis technique employed in this study is multiple linear regression analysis. The results of this study indicate that public ownership has no significant effect on firm value, managerial ownership has no significant effect on firm value, and board gender diversity has no significant effect on firm value. In contrast, firm size has a significant negative influence on firm value.